Enhancing Fiqh Learning Outcomes through 3D Animated Videos: A Study of 'Upin & Ipin' at MTsN (State Islamic Junior High School) - Maulana Firdaus , Ratio; Anwar, Khoirul; Fadilah, M. Risky (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aims to improve the learning outcomes of Fiqh on ablution material through the use of 3D animated video media